2021
DOI: 10.1088/1757-899x/1079/4/042033
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Structure of the Friction surface of PTFE / Layered Silicate Composites

Abstract: The wear of PTFE filled with layered silicates (LS) was investigated depending on the concentration and chemical nature of the fillers. The influence of these factors on the tribotechnical characteristics and the structure of the surface layers of composites is shown. Using SEM methods, it has been established that the introduction of LS contributes to the formation of a protective layer on the friction surface consisting of worn PTFE particles and a filler. The thickness of the layer does not depend on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, PTFE itself is a good lubricant, and there are three forms of PTFE falling off from the composite surface: one part falls off from the contact area and directly forms wear debris; The other part is transferred to the metal friction ring surface to form a transfer film; Another part does not break away from the contact surface or form a transfer film, but flows like a fluid along the sliding friction direction, which can reduce the friction coefficient. 50
Figure 6.Friction coefficient and volumetric wear rate of GF/MoS 2 /PTFE composites at different pressures.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PTFE itself is a good lubricant, and there are three forms of PTFE falling off from the composite surface: one part falls off from the contact area and directly forms wear debris; The other part is transferred to the metal friction ring surface to form a transfer film; Another part does not break away from the contact surface or form a transfer film, but flows like a fluid along the sliding friction direction, which can reduce the friction coefficient. 50
Figure 6.Friction coefficient and volumetric wear rate of GF/MoS 2 /PTFE composites at different pressures.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PTFE itself is a good lubricant, and there are three forms of PTFE falling off from the composite surface: one part falls off from the contact area and directly forms wear debris; The other part is transferred to the metal friction ring surface to form a transfer film; Another part does not break away from the contact surface or form a transfer film, but flows like a fluid along the sliding friction direction, which can reduce the friction coefficient. 50 Surface morphology analysis of glass fiber/ molybdenum disulfide/ polytetrafluoroethylene composites Figures 7 and 8 show, respectively, the SEM images of the GF/MoS 2 /PTFE composites before and after wear for various molding pressures. Figure 7 shows that the surface of the specimens produced without abrasion studies is smooth, devoid of obvious wear indicators such pits, furrows, and surface peeling, and the filling material is more evenly distributed throughout the matrix at lower molding pressure.…”
Section: Effect Of Different Molding Pressure Processes On the Tribol...mentioning
confidence: 99%
“…Based on the previous works conducted by such authors as Okhlopkova A.A., Sleptsova S.A. et al, and judging by the socalled "critical concentrations" that determine the maximum change in the tribological properties of a polymer composite materials, the following concentrations of filler content are selected: 2 mass% of SP and 1.5 mass% of SP + 0.5 mass% of MS [13,17]. A reason for the use of magnesium spinel as a functional additive lay in the ability of nanoparticles to selforganize, or rather that due to their activity nanodispersed particles in the mass of the polymer matrix tend to form clusters, which contributed to the reinforcement of the material leading to an increase in strength characteristics [17].…”
Section: Methodsmentioning
confidence: 99%
“…This surface layer is apparently formed mainly by wear particles appearing in large quantities at the beginning of abrasion, and falling onto the friction surface. It means that the products of wear repeatedly fall onto the friction surface, and then they are subjected to mechanochemical influence, as well as processes of dispersion, defragmentation, activation and oxidation [13]. For instance, in the work of Beliy et al it was shown that the process of friction of PCMs was accompanied by changes in the surface and near-surface layers of the composite, which led to formation of a new layer with modified characteristics, differing in physical and chemical, physical and mechanical properties from the properties of the PCM itself [18,21].…”
Section: Worn Surface Analysismentioning
confidence: 99%
See 1 more Smart Citation